2017
DOI: 10.18632/oncotarget.22144
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of semaphorin 3E promotes hallmarks of experimental chronic allergic asthma

Abstract: Guidance cues such as semaphorins are attractive novel therapeutic targets for allergic disorders. We have previously described an inhibitory effect of semaphorin 3E (Sema3E) on human airway smooth muscle cell function. We have further addressed a canonical role for Sema3E in acute model of allergic asthma in vivo. Considering the chronic nature of the disease, the potential implication of Sema3E to alleviate long-lasting deficits should be investigated. Expression of Sema3E in a chronic model of allergic asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…In an attempt to explain opposing actions of Sema3E on vasculature we explored if Sema3E can regulate inflammatory mediators (myeloid cell-derived) which exhibit distinct functions. A lack of Sema3E has been shown to aggravate inflammation ( Movassagh et al, 2017a , b ) and exacerbate neovascular retinopathy by increasing the release of pro-inflammatory cytokines, particularly the pro-angiogenic IL-17A ( Talia et al, 2016 ). As expected, IL-17A mRNA and protein (immunoreactivity) increased during the neovascular phase starting at P14 (p < 0.05) and furthermore by P17 ( P < 0.001) ( Figures 6A,B ); likewise, mRNA expression of the retinoic acid receptor-related orphan nuclear receptor γ (RORγ), a key regulator in the production of IL-17A ( Talia et al, 2016 ), also increased at P17 in OIR ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to explain opposing actions of Sema3E on vasculature we explored if Sema3E can regulate inflammatory mediators (myeloid cell-derived) which exhibit distinct functions. A lack of Sema3E has been shown to aggravate inflammation ( Movassagh et al, 2017a , b ) and exacerbate neovascular retinopathy by increasing the release of pro-inflammatory cytokines, particularly the pro-angiogenic IL-17A ( Talia et al, 2016 ). As expected, IL-17A mRNA and protein (immunoreactivity) increased during the neovascular phase starting at P14 (p < 0.05) and furthermore by P17 ( P < 0.001) ( Figures 6A,B ); likewise, mRNA expression of the retinoic acid receptor-related orphan nuclear receptor γ (RORγ), a key regulator in the production of IL-17A ( Talia et al, 2016 ), also increased at P17 in OIR ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies used in this study are DX5 (DX5), CD3 (145-2C11), CD40 (1C10), CD86 (GL1), CD80 (16–10A1), from eBiosciences (San Diego, CA, USA), and from BD Pharmingen (NJ, USA). Anti-human/mouse Sema-3E, anti-human Plexin D1 (85% cross- reactivity with mouse) ( 30 ), and mouse NRP1 antibodies were purchased from R&D system (Minneapolis, MN, USA). NK or DC was incubated with anti-Fcγ RIII (2.4 G2) before surface marker staining.…”
Section: Methodsmentioning
confidence: 99%
“…Holl et al reported that Plexin D1-deficient DC produced selectively higher level of IL-12/IL-23 p40 ( 29 ). Collectively, they further established a critical role of Sema-3E in the modulation of immune responses ( 30 ). Here, we examined formally whether Sema-3E exerts any regulatory function on NK cells in NK-DC crosstalk.…”
Section: Introductionmentioning
confidence: 91%
“…Semaphorins are originally recognised as neuronal chemorepellents and were reported to play a role in cellular activities, such as cell proliferation, migration, adhesion, and angiogenesis (Movassagh et al, 2017a). Increased AHR, airway remodeling and Th2/Th17 inflammation in chronic allergic airway disease were shown to be significantly augmented in a Sema 3E-deficient mouse model (Movassagh et al, 2017b) and therefore demonstrating an essential role of Sema 3E in suppressing hallmarks of chronic airway disease. Sema 3E and 3A expression and their receptors were reported to be expressed in both human asthmatic and non-asthmatic ASM.…”
Section: Signal Transduction Regulation In Asm Proliferationmentioning
confidence: 99%